'History Wars' and Reconciliation in Japan and Korea
XIX, 201 p. 1 illus.
Keywords: This book provides a fresh approach to understanding the origins and possible future direction of the Northeast Asia “history wars.” Leading scholars in history, literary studies, and education present the complex issue in a historical context by assessing its political and cultural dimensions, particularly with regards to relations between Japan and Korea. Their essays also touch on the significance of civil society efforts to advance peaceful reconciliation and the social and political forces that have worked to frustrate such efforts since 1945. At its core, this volume explores the political significance in the gap between Korean and Japanese civil society versus governmental efforts to resolve issues lingering from the Pacific War in Asia; the significance of cultural as well as political efforts to understanding historical and contemporary relations among Northeast Asian neighboring states; and specific factors—such as textbook reform, revised school curricula, and civil society education efforts— that are working to ameliorate the heretofore deadlocked “history wars.”.